A Textual Analysis of President Akufo-Addo’s 12th Covid–19 Address - Rockson, Kweku; Adade-Yeboah, Asuamah; Owusu, Edward (JET (Journal of English Teaching), 2023)
The study examined the social and political circumstances in Ghana which evolved because of the pandemic created by COVID-19, and the extent to which President Akufo-Addo was able to effectively use the medium of speech to manage this global health emergency. This study focused on the stylistic choices of the speech and investigated how different sentence structures, repetitions, political jargon, and other linguistic characteristics were deployed. Textual analysis involves the appreciation of a text while explaining its ideological and cultural dimensions (Fursich, 2009). This study was underpinned by the Narrative Paradigm Theory and Sociolinguistics. Under Narrative Paradigm Theory, narratives have a plot and characters that are involved in an interaction and can therefore be seen as a narrative in form and function. Sociolinguistics shows how language can be presented in specific contexts of social life, and how it reflects and then includes meaning and structure in those contexts (Schiffrin, 1997). Also, textual analysis as a qualitative research methodology was used for this study, and as an interpretive approach, it concentrated on the embedded cultural and ideological positions on the material. The findings from this study showed that the speech that was in a narrative mood incorporated all the achievements and challenges identified during the pandemic. It also provided cases of semantic analysis of words and meaning, relations among words that included metaphors, semantics, argumentative, narrative, and cognitive frames.